Falling Through the Cracks: Unmet Heath Service Needs among People Living with HIV in Atlanta, Georgia - Kalichman, Seth C. (2011)
Despite growing numbers of people living with HIV (PLWH), the landscape of related services is shrinking. This study investigated health and social service needs of men (N = 489) and women (N = 165) living with HIV in Atlanta, GA. Participants completed confidential measures asking about the health and social services they needed and accessed. Results showed an array of health and social service needs among PLWH; failure to access services was prevalent. Hunger was among the most common basic needs, reported by greater than 60% of men and women. For men, unmet service needs were associated with fewer years since testing positive for HIV, higher CD4+ T cell values, experiencing more stressors and depression, and greater quantity of alcohol use. For women, failure to access services was associated with experiencing depression and not receiving HIV medications. Providing basic services to PLWH remains a public health priority and moral imperative.